Inhibitory effect of STAT3 gene combined with CDDP on growth of human Wilms tumour SK-NEP-1 cells. Issue 3 (3rd June 2016) - Wang, Junrong; Zhang, Nina; Qu, Haijiang; You, Guangxian; Yuan, Junhui; Chen, Caie; Li, Wenyi; Pan, Feng
Abstract : To investigate the effects of signal transducer and activator of transcription 3 (STAT3) combined with cisplatin (CDDP) on the growth of human Wilms tumour (WT) SK-NEP-1 cell subcutaneous xenografts in nude mice and the possible mechanisms. Human WT SK-NEP-1 cells were subcutaneously transplanted to establish the BALB/c nude mice xenograft model. Mice were randomly divided into five groups: blank control group, adenovirus control group (NC group), STAT3 group, CDDP group and STAT3 plus CDDP group (combination group). Tumour volume and tumour weight were observed during the therapeutic process. The expression levels of STAT3, glucose regulatory protein 78 (GRP78) and BCL2-associated X protein (BAX) were evaluated by immunohistochemical analysis. Compared with the STAT3 group or CDDP group, the tumour weight and volume was significantly reduced in the combination group ( P <0.05). No statistical significance was found in NC group compared with the blank control group ( P  > 0.05). Immunohistochemical analysis showed that STAT3, GRP78 and BAX protein levels in the combination group were significantly higher than those in STAT3 group and CDDP group ( P <0.05). Exogenous STAT3 and CDDP may synergistically inhibit the xenograft tumour growth through up-regulation of BAX protein via GRP78.